Diversity technique for multiple input multiple output orthogonal frequency division multiplexing (MIMOOFDM) system using a new subcarrier mapping scheme - Idris, A. (Academic Journals, 2011)
The objective of this research is to propose a new subcarrier mapping scheme intercarrier interference self cancellation intercarrier interference self cancellation (ICI-SC) technique using data allocation in space time frequency block codes (STFBC) multiple input multiple output orthogonal frequency division multiplexing (MIMO-OFDM) system. It aims to achieve maximum diversity order and to compensate integrated effect of frequency offset (FO) for intercarrier interference (ICI) reduction in the system. Using theoretical derivation of the pairwise error probability (PEP), a simulation model is then being used to compare with adjacent and symmetric subcarrier mapping scheme with FO. The results show that the ICI contained in the received signals can be effectively reduced using a new subcarrier mapping scheme. Thus, the proposed method is using STFBC outperforms existing subcarrier mapping schemes by approximately reducing the ICI with maximum diversity order in MIMO-OFDM system.